PENGARUH PROPORSI TOMAT DAN PULP KULIT PISANG KEPOK TERHADAP SIFAT FISIKOKIMIA DAN ORGANOLEPTIK LEATHER TOMAT-PULP KULIT PISANG KEPOK - Pranata, Ignatius Ryan; Surjoseputro, Sutarjo; Setijawati, Erni (Jurnal Teknologi Pangan dan Gizi, 2017)
Tomatoes are one of agricultural commodities that have high economic value and produced throughout the year. Tomatoes production year to year always increase and reached 950.385 ton in 2011. Number of tomatoes products is still very limited providing opportunities utilization of tomatoes into fruit leather products. Fruit leather containing 10-15% of water in a form of thin sheet that can be rolled. The quaskin pulp lity of good fruit leather is plasticy, elastic, and has a good gel form of which is determined by some components especially pectin, sugar and acid. Tomato leather which is produced with 100% tomato can not form a solid gel because pectin content in tomato is 4,63%. Therefore pectin from saba banana skin pulp is added to get a good result of it. Saba banana skin pulp has a high pectin content. Pectin content in saba banana skin pulp is 5,5%. The research design used was Randomized Group Design consisting one factor which is the proportion of tomatoes and saba banana skin pulp (100%:0%; 90%:10%; 80%:20%; 70%:30%; 60%:40%; 50%:50%). The parameters analyzed include physicochemical properties (moisture content, aw, texture (flexibility), pH, and colour) and the organoleptic properties (preference for texture, colour, and flavor). The proportion use of tomato increased moisture content, texture (gel strenght), on the other hand decreasing pH, lightness, redness, and yellowness of leather. The best proportion of tomato and banana skin pulp was at 70:30 which had pH 3.38, moisture content 11.79%, texture (gel strenght) 1.12 kg, lightness 43.8, redness 28.01, yellowness 18.9 with sensory scores of flavor, color, and texture were 5.2, 5.95, and 5 respectively with score 1-7.